2020
DOI: 10.1111/1750-3841.15508
|View full text |Cite
|
Sign up to set email alerts
|

Transformations and functional role of starch during potato crisp making: A review

Abstract: Potato chips are a major product in the savory snack market and are consumed worldwide because of their enjoyable and distinctive organoleptic properties. They are conventionally produced by deep-frying thin slices of fresh potato.In contrast,potato crisps are manufactured from dried potato derivatives such as potato flakes (PFs).Their production is reviewed in this manuscript and requires the formation of dough based on hydrated PFs. Expansion of the dough during deep-frying provides the crisps with their des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 130 publications
1
5
0
Order By: Relevance
“…It showed an opposite pattern to the amylose content in the same values but with a negative correlation (r � −0.41, −0.39, and −0.37) between the frying temperature and frying time. e significant decrease in the amylopectin content along with increased frying temperature, frying time, and DSB substitution percentage was previously reported by several authors due to heat stress [29][30][31].…”
Section: Amylose and Amylopectin Contents Of Barley-soybeansupporting
confidence: 57%
“…It showed an opposite pattern to the amylose content in the same values but with a negative correlation (r � −0.41, −0.39, and −0.37) between the frying temperature and frying time. e significant decrease in the amylopectin content along with increased frying temperature, frying time, and DSB substitution percentage was previously reported by several authors due to heat stress [29][30][31].…”
Section: Amylose and Amylopectin Contents Of Barley-soybeansupporting
confidence: 57%
“…During the processing of starch-based potato crisps, a starch gel network is created that is sufficiently strong to resist expansion and avoid structural collapse during deep-frying. Reyniers et al [ 49 ], when testing potato crisps (also referred to as indirectly expanded or restructured potato chips) expanded by the frying process concluded that the replacement of water by oil explains the direct relationship between water loss and oil uptake. During frying, the water evaporates from the matrix and the oil is absorbed into the voids formed by the evaporated water.…”
Section: Resultsmentioning
confidence: 99%
“…If an overly strong internal structure is formed during processing through the use of additives, dense and hard products with small pores may form, and, hence, oil absorption is reduced. In addition, depending on processing temperature and shear intensity, gelatinization of starch occurs and further gelatinization and fast water evaporation under frying allow pronounced swelling that may affect product texture and lipid content [ 49 ]. In related experiments by Lisiecka et al [ 50 ], fresh carrot pulp addition to potato-based recipes reduced the number and pore size of crisps expanded by various applied methods.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the addition of the flakes at 10% decreased the oil content by 12%. One possible reason was that the starch of potato flakes was largely gelatinized with a high water-holding capacity (Reyniers et al, 2020). Increasing the addition level of flakes decreased the whiteness and increased the redness and yellowness of the youtiao color.…”
Section: Starch-based Floursmentioning
confidence: 99%